A New Approach for Retaining Mercury in Energy Generation Processes: Regenerable Carbonaceous Sorbents - Nuria Fernández-Miranda; Elena Rodríguez; Maria Antonia Lopez-Anton; Roberto García; Maria Rosa Martínez-Tarazona (Energies, 2017)
The energy production processes from fossil fuels represent the first anthropogenic source of mercury emissions in Europe and the second in the world. Among the different possibilities that can be posed to reduce these emissions, this work focuses on the use of regenerable sorbents based on gold nanoparticles dispersed on activated carbon foam. The use of regenerable sorbents would not only allow the objective of reducing mercury emissions, but also avoiding the generation of new toxic wastes. The results showed a retention efficiency of 100% and a retention capacity close to 600 µg·g−1 over several cycles of regeneration. Moreover, acid gases did not poison the support. It was observed that mercury capture in this simulated oxy-combustion atmosphere was a consequence of two mechanisms: (1) the amalgamation of elemental mercury and elemental gold and (2) the oxidation of elemental mercury in the presence of HCl, with the subsequent retention of the oxidized mercury on the surface of the activated carbon foam. The nanodispersion of gold on such supports involves a high initial investment. However, this would be counterbalanced by the remarkable regeneration capacity of the sorbent and the possibility of recovering all the materials used.